Work futures: globalization, planetary markets, and uneven developments in the gig economy - Anwar, Mohammad Amir; Schäfer, Susann; Golušin, Slobodan (Globalizations, 2024)
The world of work is changing rapidly in myriad ways. The processes of digitization are enabling workers from different parts of the world to compete in a global market over the Internet without moving to different locations. Many employers are opting for hybrid working solutions in light of the COVID-19 pandemic. As a result, some commentators have suggested the end of globalization, while others are hoping that a fairer society will emerge. This paper departs from such rigid assessments of the future of work and instead attempts to understand the multi-dimensional transformations in the world of work through the lens of the global gig economy. It argues that the gig economy is the latest manifestation of capitalism’s drive to accumulate which in turn produces uneven geographical developments. It concludes by outlining some strategies to build better work futures in a globalized world.
Gesehen am 24.01.2025
Online veröffentlicht: 6. August 2023